Preventive Behaviors Against Gastritis Among Female Students at Ma’had Asy-Syakur MAN 2 Kediri - Dwi Setyorini; Laviana Nita Ludyanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Adolescents require higher levels of nutrients for physical growth and development, but the current trend is for adolescents to prefer instant foods such as junk food, spicy foods and foods containing unhealthy additives. This has led to the emergence of various diseases, one of which is gastritis. This condition is even more risky for female students living in Islamic boarding schools with busy activities and irregular meal schedules, thus requiring efforts to prevent gastritis. This study aims to determine the gastritis prevention behaviour of female students at Ma'had Asy-Syakur MAN 2 Kediri. This study uses a descriptive design with one variable, namely gastritis prevention behaviour. The research population consisted of students living at Ma'had Asy-Syakur MAN 2 Kediri, with a total of 59 respondents. Data collection was conducted using a gastritis prevention behaviour questionnaire. The results showed that almost all respondents (81.36%) had gastritis prevention behaviours in the adequate category, with a small portion in the good category (18.64%). The female students' busy and well-scheduled activities, accompanied by the implementation of discipline, regular meal arrangements, and the provision of stomach-friendly menus, contributed to the formation of gastritis prevention behaviour. The most common preventive behaviour was avoiding spicy foods, due to habits, taste preferences, and socio-cultural factors that had been established. This study recommends the need for health education that not only focuses on increasing knowledge but also changing attitudes and habits so that gastritis prevention behaviour can be further optimised.